2017
DOI: 10.1016/j.jpurol.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Mucosectomy impairs ileal microcirculation and results in flap contraction after experimental ileocystoplasty

Abstract: Contraction of demucosalized intestinal flaps used for bladder augmentation has been frequently reported. This study provides direct evidence the first time for severely compromised microcirculation of the ileal flaps after mucosectomy. Limitation of the study is the relative low number of animals sacrificed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 14 publications
4
15
0
Order By: Relevance
“…In a previous study, the authors found that significant disruption of the intrinsic blood supply and microcirculation of the flaps may result in long-term ischemia and fibrosis [27]. By highlighting this, together with the current observation of damaged ENS and acute shrinkage, the authors aim to contribute to the discussion pertinent to microvascular and neuronal aspects of the valued and innovative experimental efforts to remove or replace the mucosal coverage of the gastrointestinal flaps used for augmentation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In a previous study, the authors found that significant disruption of the intrinsic blood supply and microcirculation of the flaps may result in long-term ischemia and fibrosis [27]. By highlighting this, together with the current observation of damaged ENS and acute shrinkage, the authors aim to contribute to the discussion pertinent to microvascular and neuronal aspects of the valued and innovative experimental efforts to remove or replace the mucosal coverage of the gastrointestinal flaps used for augmentation.…”
Section: Discussionmentioning
confidence: 92%
“…The limitation of this study is that the authors did not monitor the shrinkage in the long term; however, they did not observe any improvement during the 2-hours' duration of this step or part of the experiment, in each pig. In a previous animal study, where microcirculation of the mucosectomized ileal flaps was assessed before and after mucosectomy and the flaps were used for augmentation in a reverse fashion, the authors were able to demonstrate the long-term shrinkage of both types of these flaps [27].…”
Section: Discussionmentioning
confidence: 97%
“…The material for bladder augmentation should be elastic tissue with a sufficient blood supply, and its surface should be able to resist the erosive effects of urine. Cervellione observed a significant reduction in microcirculation after mucosectomy, which may result in contraction[ 14 ]. The blood supply for the bladder urothelium without detrusor and the de-epithelialized intestinal segment was damaged, and these tissues were less elastic and at a higher risk of ischemic contraction.…”
Section: Discussionmentioning
confidence: 99%
“…However, looking closer into the study we found three pigs were lost due to sepsis secondary to urine leakage at the early postoperative period, two additional pigs were lost because of urine leakage from the anastomotic line, one graft showed shrinkage among the seven surviving. Others failed to reproduce similar results with demucosalised reverse ileum flap [32]. Flap shrinkage was detected and significantly decreasing microcirculatory parameters also occurred in all animals with reversed ileal flap [32].…”
Section: The Colonmentioning
confidence: 93%
“…Further, there have been several attempts at preventing mucus secretion [31][32][33]. Cerveillone et al studied the changes in microcirculation after mucosectomy and the phenomenon of flap shrinkage in pigs.…”
Section: The Small Intestinementioning
confidence: 99%